In vivo CpG DNA/toll-like receptor 9 interaction induces regulatory properties in CD4+CD62L+ T cells which prevent intestinal inflammation in the SCID transfer model of colitis. Issue 10 (5th May 2005) - Obermeier, F; Strauch, U G; Dunger, N; Grunwald, N; Rath, H C; Herfarth, H; Schölmerich, J; Falk, W
Abstract : Background and methods: Cytosin-guanosin dinucleotide (CpG) motifs of bacterial DNA are known to be potent activators of innate immunity. We have shown previously that administration of CpG containing oligodeoxynucleotide (CpG-ODN) to mice before the onset of dextran sodium sulphate induced colitis ameliorated colitis and inhibited induction of proinflammatory cytokines. To investigate the possible involvement of CD4 + T cells in the prophylactic CpG-ODN effects, we used the SCID transfer model of colitis. Results: CD4 + CD62L + T cells from CpG-ODN treated donors did not induce significant intestinal inflammation in SCID recipients, in contrast with control cells. Additionally, cotransfer of these cells with CD4 + CD62L + cells from normal mice protected recipient animals from colitis, indicating regulatory activity. Also, CD4 + CD62L + cells from toll-like receptor 9 deficient animals induced a significantly more severe colitis in SCID recipients than cells from wild-type littermate controls, suggesting a similar protective role of "endogenous" bacterial DNA leading to a less "aggressive" phenotype of these cells. There was no detectable difference in regulatory T cell surface markers between aggressive and attenuated cell pools but attenuated cell pools showed reduced proliferation in vitro and in vivo and produced less interferon γ, interleukin (IL)-5, and IL-6 after anti-CD3 stimulation. Conclusions: Collectively, our data support the concept that both endogenous bacterial DNA and exogenously supplied CpG motifs of bacterial DNA induce regulatory properties in CD4 + T cells. Therefore, bacterial DNA derived from the normal gut flora may contribute essentially to the homeostasis between effector and regulatory immune mechanisms in healthy individuals to protect them from chronic intestinal inflammation.